Critical Review of Qur'anic Verses in the Context of Colonization - Muhammad Rum; Abdul Aziz (ANWARUL, 2025)
Grounded in the Qur’anic perspective, particularly QS. al-Hajj:39, this study examines military strength as a kifā’iyah obligation for Muslim rulers to uphold justice and combat oppression, including territorial colonization and the exploitation of natural resources for the benefit of specific groups. The research aims to elucidate the Qur’anic foundations of this obligation, clarify its implications for individual Muslims’ duty to maintain physical health as preparation for jihad fi sabilillah—as reflected in hadith stating that death without the intent to fight for truth constitutes a “death of jahiliyyah”—and analyze its contemporary relevance for Indonesia’s struggle for genuine sovereignty. Employing a thematic exegesis of relevant Qur’anic verses alongside historical analysis, the study traces Indonesia’s experience of colonialism, highlighting President Sukarno’s call to Nahdlatul Ulama (NU) scholars, Acehnese communities, and the broader Muslim population to defend the newly proclaimed independence through jihad fi sabilillah against colonial powers. The findings indicate that, in a Qur’anic framework, colonization encompasses territorial, economic, physical, and intellectual forms of injustice imposed on a nation and its people, and that the continued dominance of non-indigenous actors in managing Indonesia’s natural resources constitutes a form of contemporary colonization requiring liberation. The study further identifies three Qur’anic pillars of true national independence: impartial justice, equitable public welfare, and freedom with professional protection for adherents of recognized religions to practice their faith without discrimination. The research concludes that aligning national structures with these Qur’anic standards necessitates urgent policy reforms aimed at realizing substantive justice, fair resource governance, and comprehensive sovereignty.